Taking on a manager role can support women’s physics lab identity development - Emily M. Stump; Matthew Dew; Sophia Jeon; N. G. Holmes (Physical Review Physics Education Research, 2023)
Prior research has indicated that students in the undergraduate physics lab divide work inequitably with regard to gender. In this work, we further probed women’s experiences in lab group work, focusing on women who take on managerial and leadership roles in the lab. We interviewed and surveyed women enrolled in a sophomore-level project-based lab course, drawing on a practice-linked identity framework to characterize their opportunities for engagement and identity development within the course. Although we observed some gender inequities in group work, we also found that taking on a manager role had a positive impact on many women’s development of physics lab identity. Our results suggest that instructors should take into account women’s individual experiences and preferences for particular roles when structuring equitable group work.